1998
DOI: 10.1109/23.736536
|View full text |Cite
|
Sign up to set email alerts
|

Emerging optocoupler issues with energetic particle-induced transients and permanent radiation degradation

Abstract: Radiation-induced permanent degradation and single event transient effects for optocouplers are discussed in this paper. These two effects are independent to the first order and will be addressed separately. Displacement damage-induced degradation of optocoupler current transfer ratio is reviewed. New data are presented that show the importance of application specific testing and that generalized quantification of optocoupler CTR degradation can lead to incorrect predictions of actual circuit performance in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Previous studies in radiation induced degradation in optocouplers at room temperature indicated that the most affected parameters were CTR and dark current (1,2). This fact is also applicable to high voltage (HV) optocoupler where the working voltage could go up to 10KV.…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies in radiation induced degradation in optocouplers at room temperature indicated that the most affected parameters were CTR and dark current (1,2). This fact is also applicable to high voltage (HV) optocoupler where the working voltage could go up to 10KV.…”
Section: Introductionmentioning
confidence: 79%
“…Investigations by LaBel et al [1] and Reed et al [2] suggest that high-bandwidth optocouplers (GaAs LED and Si photodiode) are more susceptible to transient effects than low-bandwidth optocouplers. A review of single-event effects on a variety of spacebased devices was published recently with an excellent list of references [3].…”
Section: Gaas Vcsels and Photodiodesmentioning
confidence: 99%
“…Not surprisingly, when it becomes necessary to predict the life of an optocoupler circuit this information is difficult to apply. One of the key reasons is that optocoupler performance parameters and their apparent degradation depend on the circuit application, as suggested by [1] and [2]. For a complex system it is impractical to test each unique circuit application.…”
Section: Introductionmentioning
confidence: 99%